PENGARUH KUALITAS PELAYANAN, STORE ATMOSPHERE, HARGA TERHADAP KEPUASAN PELANGGAN PADA COFFESHOP SEKARUANG DI KOTA GRESIK - Insani, abdul ghofuur alif; Aslamiyah, Suaibatul (Jurnal Bisnis dan Kewirausahaan, 2025)
This study aims to examine the influence of service quality, store atmosphere, and price on customer satisfaction levels at Sekaruang Coffeeshop, Gresik City. The background of the study is based on various customer complaints, such as slow service, a store atmosphere that does not support comfort, and an imbalance between price and perceived benefits. A quantitative approach was used with a survey method through a questionnaire distributed to 120 respondents. The data obtained were analyzed using validity, reliability, normality, multiple linear regression, t-test, and coefficient of determination (R²) tests with the help of SPSS software. The results showed that service quality, store atmosphere, and price had a positive and significant effect on customer satisfaction. The coefficient of determination value of 84.5% confirms that these variables are able to explain customer satisfaction dominantly. This finding confirms that improving service quality, creating a comfortable store atmosphere, and setting appropriate prices are important factors in increasing customer satisfaction.